Effective Connectivity in Subjects With Mild Cognitive Impairment as Assessed Using Functional Near-Infrared Spectroscopy - Bu, Lingguo; Huo, Congcong; Qin, Yuexia; Xu, Gongcheng; Wang, Yonghui; Li, Zengyong (American journal of physical medicine & rehabilitation, 2019)
This study aimed to reveal the physiological mechanism in subjects with mild cognitive impairment based on effective connectivity method. Effective connectivity was assessed by dynamic Bayesian inference of the oxygenated hemoglobin concentration signals measured through functional near-infrared spectroscopy. The oxygenated hemoglobin concentration signals were recorded from the left prefrontal cortex, right prefrontal cortex, left motor cortex, right motor cortex, left occipital lobe, and right occipital lobe of 26 subjects with mild cognitive impairment (mild cognitive impairment group) and 28 healthy elderly subjects (control group) at resting state. The coupling strength of right prefrontal cortex to left prefrontal cortex (F = 7.964, P = 0.007) and left prefrontal cortex to right occipital lobe (F = 4.278, P = 0.044) in interval III as well as left prefrontal cortex to left occipital lobe (F = 5.637, P = 0.021), right occipital lobe to left prefrontal cortex (F = 4.762, P = 0.034), and right prefrontal cortex to left occipital lobe (F = 4.06, P = 0.049) in interval IV in the mild cognitive impairment group were significantly lower than those in the control group. The decreased effective connectivity levels among brain regions may be a marker of impaired cognitive function in the mild cognitive impairment group. The constructed effective connectivity network based on functional near-infrared spectroscopy provide a noninvasive method to assess mild cognitive impairment.